EFFECT OF HOT DIPPING ALUMINIZING ON THE TOUGHNESS OF LOW CARBON STEEL - Dody Prayitno; Ammar Abyan Abdunnaafi (SINERGI, 2021)
Steel that has been aluminized said as hot dipping aluminizing has better protection against corrosion and can protect against temperatures as high as 800°C. In hot dipping aluminizing, Steel is immersed into a molten aluminium for certain dipping time. The research aims to know the effect of preheating and dipping time on the toughness of low carbon steel. The method research was started by cutting the low carbon steel plate, according to ASTM E23 (Charpy test sample) into 16 pieces samples. Then the samples were grouped into four groups. Group-1 was initial samples. The Group-2 was directly immersed into molten aluminum 700 0C, for dipping time 5 minutes. The Group-3 was preheated at 700 oC for 30 minutes and then to be aluminized (700 oC) for dipping time 5 minutes. The Group-4 was preheated at 700 oC for 30 minutes and then to be aluminized (700 oC) for dipping time 10 minutes. Finally, all groups were tested by the Charpy test at room temperature. The results show that the aluminizing increases the toughness of low carbon steel from 228.125 KJ/m2 to 312.5 KJ/m2. The preheating process before aluminizing increases sharply the toughness of low carbon steel from 228.125 KJ/m2 to 512.5 KJ/m2. The increasing dipping time from 5-minute to 10-minute increase gradually the toughness from 512.5 KJ/m2 to 556.25 KJ/m2.